2014
DOI: 10.3109/13880209.2014.937504
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia kolaseed ameliorates renal, hepatic, and testicular oxidative damage in streptozotocin-induced diabetic rats

Abstract: The findings from this investigation provide persuasive scientific support for the traditional use of G. kola seed in the treatment of diabetes and its associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 46 publications
2
34
0
1
Order By: Relevance
“…The reduction in testicular weight observed in this study is a pointer to codeine-induced alteration in metabolic process that could be associated with excessive tissue break down [40,41]. Studies have reported the possibility of assessing organ toxicity by the organ weight [42,43].…”
Section: Discussionmentioning
confidence: 89%
“…The reduction in testicular weight observed in this study is a pointer to codeine-induced alteration in metabolic process that could be associated with excessive tissue break down [40,41]. Studies have reported the possibility of assessing organ toxicity by the organ weight [42,43].…”
Section: Discussionmentioning
confidence: 89%
“…Male reproductive function is a targeted physiological process mostly damaged by diabetes [18] due to the high susceptibility of testicular microenvironment to oxidative stress. The commonest of non-lethal complications in diabetic men is infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Seed administration significantly ameliorates hyperglycemia-mediated damage by decreasing the blood glucose level, enhancing the antioxidant system, inhibiting lipid peroxidation, and improving the architecture of the kidney, liver, and testes in STZ-induced diabetic rats (Adedara et al, 2014). Seed administration significantly ameliorates hyperglycemia-mediated damage by decreasing the blood glucose level, enhancing the antioxidant system, inhibiting lipid peroxidation, and improving the architecture of the kidney, liver, and testes in STZ-induced diabetic rats (Adedara et al, 2014).…”
Section: Bitter Kolamentioning
confidence: 99%
“…The extracts of the seed, commonly known as "bitter kola" (Figure 28.6), have been used in African herbal medicine for the treatment of illnesses such as laryngitis, liver diseases, cough, hoarseness of voice, and diabetes and its associated complications (Adedara et al, 2014;Akinmoladun et al, 2015). The extracts of the seed, commonly known as "bitter kola" (Figure 28.6), have been used in African herbal medicine for the treatment of illnesses such as laryngitis, liver diseases, cough, hoarseness of voice, and diabetes and its associated complications (Adedara et al, 2014;Akinmoladun et al, 2015).…”
Section: Bitter Kolamentioning
confidence: 99%